Optimization and characterization of mushroom-derived flocculants for reducing turbidity in clay suspensions - Aghareed M. Tayeb; Reham H. Othman; Nasser A. M. Barakat; Aliaa M. Monazie; Mohamed A. Mahmoud (Discover Sustainability)
Abstract In the present study, a commercially available mushroom plant is used as a natural flocculent at different dosages to treat a synthetic suspension containing different concentrations of local clay. Response Surface Methodology (RSM) is used to optimize the values of operating parameters based on residual turbidity and turbidity removal percentage reduction. The highest percentage reduction in water turbidity was obtained at a pH of 6.7. The lowest value for residual turbidity (11.1 NTU) is achieved by a clay suspension with initial concentration of 1000 ppm, and the highest value for residual turbidity (22 NTU) is achieved by a clay suspension with initial concentration of 6000 ppm. The optimum values of mushroom dose were 0.2 and 0.1 g for clay concentrations 4000 and 5000 ppm, respectively, after a time of 120 min of settling. Response Surface Methodology (RSM) is used to optimize the values of the operating parameters and the results of the model fitted well with the experimental results.